2020
DOI: 10.1186/s13662-020-03137-3
|View full text |Cite
|
Sign up to set email alerts
|

Crowding effects on the dynamics of COVID-19 mathematical model

Abstract: A disastrous coronavirus, which infects a normal person through droplets of infected person, has a route that is usually by mouth, eyes, nose or hands. These contact routes make it very dangerous as no one can get rid of it. The significant factor of increasing trend in COVID19 cases is the crowding factor, which we named “crowding effects”. Modeling of this effect is highly necessary as it will help to predict the possible impact on the overall population. The nonlinear incidence rate is the best approach to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 29 publications
(36 reference statements)
0
15
0
3
Order By: Relevance
“…In the future work, we plan to incorporate the COVID-19 models to our model following the recent works [ 45 – 49 ] to have the pandemic impact on the ecological results. To model and analyze the density of the species using fractional order derivative following the recent investigations in [ 50 – 53 ] and along with the idea herein could be a next research avenue.…”
Section: Discussionmentioning
confidence: 99%
“…In the future work, we plan to incorporate the COVID-19 models to our model following the recent works [ 45 – 49 ] to have the pandemic impact on the ecological results. To model and analyze the density of the species using fractional order derivative following the recent investigations in [ 50 – 53 ] and along with the idea herein could be a next research avenue.…”
Section: Discussionmentioning
confidence: 99%
“…Although individual and household-level data linking depressive symptoms and overcrowding to Covid-19 history may be limited, the global literature has established that the Covid-19 pandemic itself may be associated with a greater level of depressive symptoms among adults 28 , 29 , 30 and that its trajectory may be influenced by overcrowding 31 , 32 , 33 potentially worsening health disparities according to race, ethnicity and socioeconomic status 12 . Whereas depressive symptoms may be manifestations of stress, which in turn, could adversely affect immune response against microorganisms, including SARS-CoV-2, overcrowding may increase the opportunity for SARS-CoV-2 exposure potentially leading to a greater frequency of Covid-19 as the number of household members residing with older adults increases.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that mediation strategies such as intensive contact tracing followed by quarantine and isolation can effectively curtail the transmission risk and the control reproduction number. In ( Zhang et al, 2020 ), Zhang and his collaborators thought that the increase in new cases of COVID-19 is due to crowding factor. They developed a mathematical model by using a nonlinear incidence rate and taking into account the aforementioned factors.…”
Section: Introductionmentioning
confidence: 99%